Impact of serum 1, 5-anhydro-d-glucitol level on prediction of major adverse cardiac and cerebrovascular events in non-diabetic patients without coronary artery disease. (October 2016) - Ikeda, Nobutaka; Hara, Hisao; Hiroi, Yukio; Nakamura, Masato
Abstract: Background and aims: Increasing evidence has demonstrated that postprandial hyperglycemia and fluctuation of glucose level affect cardiovascular events. The serum 1, 5-anhydro- d -glucitol (1, 5-AG) level rapidly decreases concomitantly with urinary glucose excretion in hyperglycemia and is a useful clinical marker of short-term glycemic status. However, there is few established evidence regarding the predictive value of 1, 5-AG for cardiovascular events in individuals without diabetes mellitus (DM). The aim of this study is 1) to prove predictive value of 1, 5-AG for cardiovascular events in high risk population, and 2) the predictive value is true of even in non-diabetic population. Methods: Serum 1, 5-AG values and coronary angiograms of 889 patients were evaluated. The study patients were divided into two groups (1, 5-AG<10.0 μg/ml-group and 1, 5-AG≥10.0 μg/ml-group) by their measured 1, 5-AG values. They were followed-up and information regarding major adverse cardiac and cerebrovascular events (MACCE) was collected. MACCE consists of all causes of death, stroke, non-fatal myocardial infarction and cardiovascular hospitalization. Results: During the follow-up period (757 ± 357days), 216 patients presented with MACCE. In all patients, the 1, 5-AG <10.0 μg/ml -group demonstrated significantly higher risk of MACCE (adjusted hazard ratio 1.63). Even in non-DM patients without coronary artery disease, the 1, 5-AG <10.0 μg/m-group showed significantly higher risk of MACCE (adjusted hazard ratio 2.34). Similar results were found even if the events were limited to: all cause death, non-fatal myocardial infarction and stroke (adjusted hazard ratio 4.07) or all cause death (adjusted hazard ratio 3.54). Conclusions: Serum 1, 5-AG value predicts MACCE even in non-DM patients without coronary artery disease. Highlights: Lower 1, 5-anhydro-d-glucitol (1, 5-AG) values are associated with higher prevalence of coronary artery disease (CAD). 1, 5-AG predicts major adverse cardiac and cerebrovascular events (MACCE) in non-diabetes mellitus patients without CAD. 1, 5-AG < 10μg/ml is strongly associated with cardiovascular events.